A financially stressed euro area - Marcus Kappler; Frauke Schleer (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
The authors analyse 149 newly compiled monthly time series on financial market stress conditions in the euro area. With the aid of a factor model they find different sources of financial stress that are important for selecting and preparing the appropriate policy response. The existence of a 'Periphery Banking Crisis' factor, a 'Stress' factor and a 'Yield Curve' factor seems to explain the bulk of volatility in recent euro area financial sector data. Moreover, by a real-time forecasting exercise, the authors show that including additional factors-that reflect financial sector conditions-improves forecasts of economic activity at short horizons.
Keywords: C38; G01; 330; financial stress; dynamic factor models; financial crisis; euro area; forecasting